Determinants of social networking software acceptance: a multi-theoretical approach - Shittu, Ahmed Tajudeen; Madarsha, Kamal Basha; Nik Abdul Rahman , Nik Suryani; Tunku Ahmad, Tunku Badariah (Universiti Malaya, 2013)
Understanding reasons why students use social media has become a major preoccupation of researchers in recent time due to the rate of its adoption among the present generation of students. Some of the few study on social media phenomenon employed a single theory as a framework in order to understand the factors that influence the acceptance of it among the students. However, in this study, acceptance to use social network software was research into through a multi-theoretical approach. Factors from innovation diffusion theory, technology acceptance model, and social influence theory were used as a conceptual framework of this study. 500 undergraduate students participated in the study. Survey questionnaires were administered on the participants. Structural equation modeling was use to analyzed the data generated from the study. A model was developed from the study known as social network software acceptance model. The findings of the study showed the interaction that exists among factors from different theories as it influences student acceptance of SNS. From the findings of this study, theoretical as well as education implications were drawn. The study concludes that acceptance of SNS is a function of interrelated factors from different theories.